2020
DOI: 10.57046/oumr1490
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of calcium hypochlorite (65% chlorine disinfectant) on the liver, brain, and gill of Clarias gariepinus fingerlings (Burchell, 1822)

Abstract: The acute toxicity of Calcium Hypochlorite was investigated on the water quality and histopathology of liver, brain and gill of Clarias gariepinus fingerlings. Fish with average weight and length of 5.5 ± 0.8g and 7.8 ± 0.5cm were stocked at 10 fish per tank and fed with 45% crude protein diets. The experimental fish was exposed to a photoperiod of 12 hours daylight and 12 hours darkness. After the range finding test, the fingerlings were exposed to test concentrations of treatments 0.000 mg/L (A), 0.011 mg/L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…37 During exposure to toxicants in aquatic organisms, the liver often accumulates lesions and undergoes histopathological alterations, as reported by Kolawole and Iyiola. 69 Several researchers have also observed similar effects and have utilized liver histopathology as reliable biomarkers in their studies on contaminants, as documented by Sadeghi et al 51 and Stoyanova et al 70 This is because the liver plays a significant role in fish physiology, contributing to anabolism (protein, lipid, carbohydrate synthesis) and catabolism (glycogenolysis, detoxification), and also serves as a storage site for various substances, particularly glycogen, as highlighted by Padrilah et al 50 Such studies have been incorporated into national surveys and monitoring programs concerning aquatic environments and biological impacts in many developed countries, as described by Sousa et al 71 In their study on copper accumulation, Padrilah et al 50 investigated the toxicity effects of fish liver histopathology and observed the degeneration of numerous hepatocytes. Inflammatory changes in liver alterations are considered significant indicators of pollutant exposure, providing valuable information on the overall health and condition of fish, as emphasized by Agbohessi et al 72 In summary, the observed structural aberrations in the liver of T. guineensis exposed to different concentrations of surfactants indicate varying degrees of toxic effects on the liver tissue.…”
Section: Histological Changes In Livermentioning
confidence: 99%
“…37 During exposure to toxicants in aquatic organisms, the liver often accumulates lesions and undergoes histopathological alterations, as reported by Kolawole and Iyiola. 69 Several researchers have also observed similar effects and have utilized liver histopathology as reliable biomarkers in their studies on contaminants, as documented by Sadeghi et al 51 and Stoyanova et al 70 This is because the liver plays a significant role in fish physiology, contributing to anabolism (protein, lipid, carbohydrate synthesis) and catabolism (glycogenolysis, detoxification), and also serves as a storage site for various substances, particularly glycogen, as highlighted by Padrilah et al 50 Such studies have been incorporated into national surveys and monitoring programs concerning aquatic environments and biological impacts in many developed countries, as described by Sousa et al 71 In their study on copper accumulation, Padrilah et al 50 investigated the toxicity effects of fish liver histopathology and observed the degeneration of numerous hepatocytes. Inflammatory changes in liver alterations are considered significant indicators of pollutant exposure, providing valuable information on the overall health and condition of fish, as emphasized by Agbohessi et al 72 In summary, the observed structural aberrations in the liver of T. guineensis exposed to different concentrations of surfactants indicate varying degrees of toxic effects on the liver tissue.…”
Section: Histological Changes In Livermentioning
confidence: 99%